“Estrategias basadas en la colaboración para el desarrollo del proceso didáctico en el área de Ciencias Naturales desde la interculturalidad” - Masabanda Simaluisa, Nilda Katherin (2022)
The research proposes an analysis of strategies based on collaboration and its impact on collaborative learning within the educational process. This demands new skills to respond to current needs, focusing on potential development that produces high levels of student participation. The objective of this research is to demonstrate the use of strategies based on collaborative work that allows reinforcing the didactic process to obtain significant learning in the area of Natural Sciences from interculturality, respecting customs, traditions, knowledge, to obtain high-quality teaching. level and inclusive. The methodology was based on qualitative research since it follows the stages: preparatory, field, analytical, it is descriptive, documentary and bibliographical, the applied method is heuristic, the technique is the interview directed to two teachers and an authority. To try to fill the gaps, a systematic review was carried out where the results made it possible to demonstrate the existing gaps within the institution in the area of Natural Sciences in the use of collaborative strategies (interdisciplinary projects), within the didactic and intercultural process. This experience provides applicable information in the teaching-learning processes that are developed through ancestral knowledge from interculturality, which contribute to the development of cognitive, procedural and attitudinal skills in students.